Multicultural-Based Character Education at Madrasah Aliyah Al-Furqan Laro, Burau District, East Luwu Regency - Abdul Muthalib; Sampara Palili; Arni Puspita Sari (Edusoshum : Journal of Islamic Education and Social Humanities, 2025)
In the context of Indonesia's multicultural society, multicultural-based character education becomes a relevant and strategic approach to instill values of tolerance, justice, and togetherness amidst ethnic, cultural, and religious diversity. This study aims to describe the implementation of multicultural-based character education and to identify the supporting and inhibiting factors in its implementation at Madrasah Aliyah Al-Furqan Laro, Burau District, East Luwu Regency. This study uses a qualitative approach with a phenomenological method. Data collection techniques include observation, in-depth interviews, and documentation, with informants consisting of the head of the madrasa, teachers, and students. The research results show that multicultural-based character education is implemented through inclusive learning, habituation of tolerance values in school activities, and the exemplary behavior of teachers in building a school culture that appreciates differences. The main supporting factors come from the social diversity of students, the commitment of teachers and school principals, and the community environment that is open to pluralism. Meanwhile, the obstacles faced include the lack of theoretical understanding among teachers regarding multicultural education, minimal professional training, and low parental involvement. This research concludes that the success of multicultural character education is greatly determined by the synergy between schools, families, and communities in creating an inclusive and transformative educational ecosystem